2000
DOI: 10.5204/mcj.1880
|View full text |Cite
|
Sign up to set email alerts
|

Capitalistic Ideology as an 'Interpersonal Game'

Abstract: "Outwit, Outplay, Outlast" "All entertainment has hidden meanings, revealing the nature of the culture that created it" ( 6). This quotation has no greater relevance than for the most powerful entertainment medium of all: television. In fact, television has arguably become part of the "almost unnoticed working equipment of civilisations" (Cater 1). In other words, TV seriously affects our culture, our society, and our lives; it affects the way we perceive and approach reality (see Cantor and Cantor, 1992… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This result was also observed in the RRc variables in NGC 4590 (M68) by Clement, Ferance & Simon (1993). The general nature of this aspect of the variation of φ31 with metallicity has previously been used to estimate the metallicity of RRc stars in the OGLE surveys of the galactic bulge (MSB98) and toward 47 Tuc (Morgan & Dickerson 2000), however these results were at best only general approximations of [Fe/H].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…This result was also observed in the RRc variables in NGC 4590 (M68) by Clement, Ferance & Simon (1993). The general nature of this aspect of the variation of φ31 with metallicity has previously been used to estimate the metallicity of RRc stars in the OGLE surveys of the galactic bulge (MSB98) and toward 47 Tuc (Morgan & Dickerson 2000), however these results were at best only general approximations of [Fe/H].…”
Section: Introductionmentioning
confidence: 55%
“…Data from the variables in this cluster were collected from the Fourier coefficient website (Morgan 2003) and an initial data set was selected based upon the method of observation, where recent, CCD based coefficients were favored over pho- tographic observations. These included Fourier coefficients from Morgan & Dickerson (2000), and Olech et al (2003). As with the globular cluster variables used to derive equations 3 and 4, the RRc stars in ω Cen were examined and poor quality fits or sparse light curves were excluded.…”
Section: Test Of the [Fe/h] Relationsmentioning
confidence: 99%
“…He identifies a similar pattern at two sites near 2700 m (9000 ft) on the Fishlake Plateau, with site use switching to a residential focus and more intensive exploitive patterns between about 1700 and 700 BP (Janetski, 2010). Morgan et al (2012) identify a nearly identical pattern developing above treeline at a site known as Pharo Heights, at 2865 m (9400 ft) in south-central Utah's Pahvant Range ca. 1700 BP.…”
Section: Regional Comparisonsmentioning
confidence: 94%
“…An analysis of a stratified-random sample of 833 flakes distributed between the six lodges excavated in 2010 and 2011 indicates debris from biface retouch and manufacture dominates the debitage assemblage. Like debitage from most other high-elevation contexts (e.g., Morgan et al, 2012;Thomas 1982), most waste flakes (58.6%) represent small, very late-stage core reduction, biface thinning, and pressure retouch (Figure 4). Interestingly, though sample size is fairly small and the distribution of diagnostic flake types appears similar between lodges (Table 2), the difference in debitage assemblages between lodges is statistically significant (p = 0.0105, Fisher's exact test).…”
Section: Flaked Stonementioning
confidence: 99%
“…Following this publication, there have been some very interesting studies all from the Meyer's group in JĂŒlich. [ 101–103 ] In particular, this team focused on the impact of the native tunnel barrier between CoPd contacts (PCoPd≅25%${P_{{\rm{CoPd}}}} \cong 25\% $) [ 101,102 ] and a (single and multiwall) carbon nanotube on the amplitude of the MR effects. They showed that the MR increases when the contacts are resistive (>100 kΩ) especially at low temperatures compared to simple ohmic contacts whose resistance does not vary much with temperature.…”
Section: Spin Transport Experiments In Carbon Nanotubesmentioning
confidence: 99%